ESTUDO DE CASO: COLETA E LOGÍSTICA REVERSA PARA LÂMPADAS FLUORESCENTES NO MUNICÍPIO DE FRANCA, SP - Melo Júnior, Tadeu Artur; Dândaro, Fernando; Ambroseto, Gismeire; Tabah, June (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707460 Fluorescent lamps are really useful products for the nowadays society. However, misdisposal of these objects can generate serious environmental damage. Reverse logistics allows companies to maximize the use of resources, enhance their corporate image, gain marketing advantages, increase economic value to their products, fulfill the current legislation and satisfy the expectations of the society. This study aims to characterize fluorescent lamps, describe the importance of reverse logistics application in companies and show the findings of a study on collect, selection and transport of this products in Franca, SP. Suggestions on how to improve the current reverse logistics process on that field are presented, together with theoretical framework and a case study. These suggestions could help to correctly standardize the whole process, reduce considerably the volume of dangerous waste in the environment and reintegrate all the components of the fluorescents lamps into the production cycle. This study is significant since its propositions meet the current environmental regulations in the country, it promotes also economic benefit to the companies involved and improvements in the environment where applied.